Influence of River‐Induced Fronts on Hydrocarbon Transport: A Multiplatform Observational Study. Issue 5 (8th May 2018) - Androulidakis, Yannis; Kourafalou, Vassiliki; Özgökmen, Tamay; Garcia‐Pineda, Oscar; Lund, Björn; Le Hénaff, Matthieu; Hu, Chuanmin; Haus, Brian K.; Novelli, Guillaume; Guigand, Cedric; Kang, HeeSook; Hole, Lars; et al.
Abstract: The Taylor Energy Site is located in the vicinity of the Mississippi Delta region over the Northern Gulf of Mexico (NGoM). Surface oil patches have been persistently observed within this site since 2004, when an oil rig was destroyed by Hurricane Ivan. A multiplatform observational experiment was conducted in April 2017 to investigate, for the first time, the main hydrocarbon pathways from the Taylor Energy Site toward the NGoM continental shelves, and the Gulf interior, under the influence of local and regional physical processes. Results indicate that the Mississippi River (MR)‐induced fronts over the Taylor Energy Site, in combination with local circulation, prevailing winds and broader regional dynamics determine the hydrocarbon transport. The drifters deployed during the field experiment, in tandem with satellite data, drone imagery, wind measurements, and radar‐derived data, efficiently described three major hydrocarbon pathways, associated with MR plume dynamics (downstream/upstream coastal currents) and basin‐wide circulation (offshore pathway). Two different types of drifters, drogued and undrogued, showed clearly different pathways, which suggest potential differences in the expected advection of oil, depending on whether it forms a surface slick or whether it is partially mixed below the surface. The existence of multiple river fronts influenced the fate of oiled waters, preventing the hydrocarbons from reaching the Delta, like a natural boom barrier, trapping and directing the oil either westward or eastward. Thermohaline measurements showed that the MR plume near Taylor was 5–10 m deep, while the clearer ocean was characterized by a 40 m upper ocean homogenous layer. Key Points: Investigation of hydrocarbon pathways over Northern Gulf of Mexico: observational study Influence of river‐induced fronts on oil transport Identification of three potential hydrocarbon pathways under the influence of Mississippi River plume, wind conditions, and ocean dynamics